Self-Esteem and Academic Engagement Among Adolescents: A Moderated Mediation Model - Zhao, Ying; Zheng, Zeqing; Pan, Chenchen; Zhou, Lulu (Frontiers in Psychology, 2021)
As an important predictor of academic achievement and an effective indicator of learning quality, academic engagement has attracted the attention of researchers. The present study explores the relationship among adolescent self-esteem and academic engagement, the mediating effect of academic self-efficacy, and the moderating effect of perceived social support. Four-hundred and eighty adolescents (Mage = 14.92) from the Hebei Province of China were recruited to complete anonymous questionnaires. The results show that self-esteem positively predicted adolescent academic engagement through the indirect mediating role of academic self-efficacy, and the percentage of this mediation effect of the total effect was 73.91%. As a second-stage moderator, perceived social support moderated the mediating effect of academic self-efficacy. Specifically, when students felt more perceived social support, the impact of academic self-efficacy on their academic engagement was greater. Our findings suggest that adolescent self-esteem, academic self-efficacy, and perceived social support are key factors that should be considered together to improve adolescent academic engagement. Therefore, parents and school educators should actively guide adolescents to improve their self-esteem and academic self-efficacy. Parents and educators should also construct an effective social support system to improve students’ perceived social support and enhance their academic engagement.